Event reconstruction performance of the ALICE high level trigger for p + p collisions - Richter, Matthias; Aamodt, K.; Alt, T.; Appelshauser, H.; Arend, A.; Becker, B.; Bottger, S.; Breitner, T.; Busching, H.; Cicalo, C.; Chattopadhyay, S.; Cleymans, J.; et al. (IEEE transactions on nuclear science, 2011)
The ALICE High Level Trigger comprises a large computing cluster, dedicated interfaces and software applications. It allows on-line event reconstruction of the full data stream of the ALICE experiment at up to 25 GByte/s. The commissioning campaign has passed an important phase since the startup of the Large Hadron Collider in November 2009. The system has been transferred into continuous operation with focus on the event reconstruction and first simple trigger applications. The paper reports for the first time on the achieved event reconstruction performance in the ALICE central barrel region.